The problems of the method of teaching descriptive geometry - Kussebayev, Ualikhan; Tuleuova, Gulmarzhan (Рroblems of engineering and professional education, 2023)
The role of software in the process of studying graphic disciplines and the impact of the results of the acquired knowledge and acquired work skills on preparing students for professional activity are considered in the article.